PROBLEM KOMUNIKASI WIRELESS SENSOR NETWORKS UNTUK PEMANTAUAN EKOLOGI LINGKUNGAN - Teguh, Rony (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
In this paper, our system development of wireless sensor network for ecology monitoring inpeatland environment. In the development the real field, topology of sensor nodes deployed in thepeatland condition. The pratical problem such as aysmteric link communication, unrealible linkcommunication, Fresnel zone problem and data packet routing can impact in the wireless sensor networkin sparse development. In this paper, our proposes identification of implementation issues incommunication practical in the focus on sparse deployment and implementation in the real environmentfor monitoring ecology.